2021
DOI: 10.1017/dmp.2021.129
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 1738 Patients With Coronavirus Disease 2019 (COVID-19) in Wuhan, China

Abstract: OBJECTIVE: Since December 2019, SARS-CoV-2 has been discovered in Wuhan and spread rapidly across China and worldwide. Characteristics of infected patients are needed to get insight into the full spectrum of the disease. METHODS: Epidemiological and clinical information of 1738 diagnosed patients during February 7-26, 2020 in Wuhan Dongxihu Fangcang Hospital were analyzed. 709 patients were followed up on symptom, mental health, isolation site, and medication after discharge. RESULTS: There were 852 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The major cause of death in patients with COVID-19 is hypoxic respiratory failure due to a combination of parenchymal and vascular changes, similar to those encountered in acute respiratory distress syndrome (ARDS) due to other causes 101 . However, several studies have suggested possibly specific features in ARDS caused by COVID-19 (refs 38 , 102 ).…”
Section: Pulmonary Vascular Pathobiology In Covid-19mentioning
confidence: 99%
“…The major cause of death in patients with COVID-19 is hypoxic respiratory failure due to a combination of parenchymal and vascular changes, similar to those encountered in acute respiratory distress syndrome (ARDS) due to other causes 101 . However, several studies have suggested possibly specific features in ARDS caused by COVID-19 (refs 38 , 102 ).…”
Section: Pulmonary Vascular Pathobiology In Covid-19mentioning
confidence: 99%
“…One study was a survey that included patient data from two regions, Hong Kong and mainland China, separately, so we analyzed the data separately ( 71 ). Twenty-two studies were conducted in China ( 27 , 31 34 , 37 , 39 , 40 , 44 , 47 , 55 , 62 65 , 67 , 69 73 , 75 77 ), six in Saudi Arabia ( 18 , 21 23 , 25 , 26 ), five in India ( 10 , 41 , 46 , 60 , 61 ), three in the United States ( 35 , 42 , 45 ) and three in Turkey ( 38 , 49 , 66 ), and these were the most frequent countries included in this review. Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 65 , 67 , 69 73 , 75 77 ), functional food (supplements) or herbs ( n = 20) ( 17 24 , 29 , 36 , 38 , 43 , 49 52 , 57 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation